Cigarette Smoke Activates the Proto-Oncogene c-Src to Promote Airway Inflammation and Lung Tissue Destruction - Geraghty, Patrick; Hardigan, Andrew; Foronjy, Robert F. (American journal of respiratory cell and molecular biology, 2014)
The diagnosis of chronic obstructive pulmonary disease (COPD) confers a 2-fold increased lung cancer risk even after adjusting for cigarette smoking, suggesting that common pathways are operative in both diseases. Although the role of the tyrosine kinase c-Src is established in lung cancer, less is known about its impact in other lung diseases, such as COPD. This study examined whether c-Src activation by cigarette smoke contributes to the pathogenesis of COPD. Cigarette smoke increased c-Src activity in human small airway epithelial (SAE) cells from healthy donors and in the lungs of exposed mice. Similarly, higher c-Src activation was measured in SAE cells from patients with COPD compared with healthy control subjects. In SAE cells, c-Src silencing or chemical inhibition prevented epidermal growth factor (EGF) receptor signaling in response to cigarette smoke but not EGF stimulation. Further studies showed that cigarette smoke acted through protein kinase C α to trigger c-Src to phosphorylate EGF receptor and thereby to induce mitogen-activated protein kinase responses in these cells. To further investigate the role of c-Src, A/J mice were orally administered the specific Src inhibitor AZD-0530 while they were exposed to cigarette smoke for 2 months. AZD-0530 treatment blocked c-Src activation, decreased macrophage influx, and prevented airspace enlargement in the lungs of cigarette smoke-exposed mice. Moreover, inhibiting Src deterred the cigarette smoke-mediated induction of matrix metalloproteinase-9 and -12 in alveolar macrophages and lung expression of cathepsin K, IL-17, TNF-α, MCP-1, and KC, all key factors in the pathogenesis of COPD. These results indicate that activation of the proto-oncogene c-Src by cigarette smoke promotes processes linked to the development of COPD.